TEACHING SPEAKING USING SHAKE CHOPSTICKS GAME - Ayu Hartini; Wulan Tripuspita (IKIP Siliwangi, 2019)
This study was conducted to improve speaking skill of the first grade at SMP N 1 Pangkalan. The game was proposed in the teaching of speaking, because that is attracting and interesting, especially for students' speaking skill. The improvement of the students' score can be seen in the increased of the students' speaking from the preliminary study (pre-test) and the score after the implementation (post-test) of the teaching speaking using shake chopsticks game. This research used a pre-experiment method by using one group pre-test and post-test design. The subject of this research were VII students of SMP N 1 Pangkalan of the 2017/2018 academic years. The finding showed that the students' score of speaking increased after being taught by using shake chopsticks game. This indicates that the use of shake chopsticks game is effective in improving students’ speaking ability. Keywords: Speaking skill, game, shake chopticks game